Effects of Sustained Silent Reading on Eighth-Grade Students' Reading Comprehension: A Quasi-Experimental Study - Asti Fitra Auliya; Abdul Kamaruddin; Zarkiani Hasyim; Nur Sehang Thamrin (MASI Mandiri Edukasi, 2026)
This study aims to determine whether the Sustained Silent Reading (SSR) method is effective in improving the reading comprehension of grade VIII students at SMP Negeri 1 Banawa Tengah. This study used a quasi-experimental design with two groups: the experimental group (VIII D) and the control group (VIII A). Both groups were given a pre-test and a post-test of the same type, consisting of multiple-choice, true/false, and detail questions that focused on literal understanding of the narrative text. The experimental group received the SSR method for six sessions, while the control group learned using the conventional method. The results showed a significant improvement in students' reading comprehension after the implementation of SSR. The average pre-test score of the experimental group increased from 44.64 to 74.68 in the post-test, while the control group increased from 42.71 to 63.46. The results of the t-test analysis showed that the t-counted value (3.82) was greater than the t-table value (1.675) at the 0.05 significance level, indicating that the alternative hypothesis is accepted. Thus, the application of the Sustained Silent Reading method has proven effective in improving the reading comprehension of grade VIII students at SMP Negeri 1 Banawa Tengah.